Mandibular sporadic Burkitt lymphoma in an adult patient: A case report and review of the literature - Azimi, Nahal (Clin Case Rep, 2021)
Only a minor percent of lymphomas arise in the oral cavity. Although rare, dentists and clinicians should not neglect them as a possible consideration in the differential diagnosis of oral lesions.